2022
DOI: 10.3390/nu14122425
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dietary Supplement Combining Bioactive Peptides and Magnesium on Adjustment Disorder with Anxiety: A Clinical Trial in General Practice

Abstract: Anxiety is a high frequency disorder in the general population. It is usually treated with benzodiazepines, which cause side effects and a dependence that could make withdrawal difficult. Alternative treatments are therefore needed to reduce the use of anxiolytics, particularly for adjustment disorder with anxiety. An observational, multicentre, prospective, longitudinal study has been conducted by general practitioners and one gynaecologist to evaluate the efficacy of a dietary supplement on adjustment disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In this study, we collected the data of 214 patients from the Wuhan Institute of Dermatology and Venereology between January 2020 and January 2022, including demographic data, disease diagnosis, Hamilton Anxiety Rating Scale (HAMA) ( 18 ), and anxiety outcome. According to the anxiety assessment results of the included samples, patients were divided into an anxiety group (n=50) and a nonanxiety group (n=164).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we collected the data of 214 patients from the Wuhan Institute of Dermatology and Venereology between January 2020 and January 2022, including demographic data, disease diagnosis, Hamilton Anxiety Rating Scale (HAMA) ( 18 ), and anxiety outcome. According to the anxiety assessment results of the included samples, patients were divided into an anxiety group (n=50) and a nonanxiety group (n=164).…”
Section: Methodsmentioning
confidence: 99%
“…The HAMA was developed by Hamilton in 1959 and includes 14 items ( 18 , 19 ): (I) anxiety mood; (II) tension; (III) fear; (IV) insomnia; (V) cognitive function; (VI) depression mood; (VII) somatic anxiety (muscle system symptoms); (VIII) sensory system symptoms; (IX) cardiovascular system symptoms; (X) respiratory system symptoms; (XI) gastrointestinal and digestive tract symptoms; (XII) reproductive and urinary system symptoms; (XIII) autonomic nervous system symptoms, and (XIV) behavior when talking to people. In this study, 2 trained assessors jointly evaluated patients with the HAMA through conversation and observation.…”
Section: Methodsmentioning
confidence: 99%
“…[12] In another study, it was found that dietary supplements showed better results in managing adjustment disorder as compared to benzodiazepines. [13] Studies conducted by Oliha and Audu (2010) on Adolescents with maladjustment, reveal that Rational Emotive Therapy and Systematic desensitization were effective in promoting emotional adjustment. [14] Recent case series by Karunakaran et al, reveal that maladjustment can be effectively treated by Homoeopathic medication.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The differences in the concentrations of Ca and Mg were not significant. On the other hand, there is evidence of the efficacy of a dietary supplement with magnesium on adjustment anxiety disorders [ 23 ].…”
Section: Introductionmentioning
confidence: 99%